2023
DOI: 10.1182/bloodadvances.2022008240
|View full text |Cite
|
Sign up to set email alerts
|

Peri–CAR-T practice patterns and survival predictors for all CAR-T patients and post–CAR-T failure in aggressive B-NHL

Abstract: Most patients receiving CAR T-cell therapy (CAR-T) for aggressive B-cell lymphoma (B-NHL) will not experience a durable remission. There are several novel agents approved for the treatment relapsed, refractory aggressive B-NHL; however, it remains unclear how to sequence these therapies pre- and post-CAR-T (peri-CAR-T). We conducted a multicenter retrospective analysis for the purpose of describing peri-CAR-T practice patterns and survival predictors for patients receiving CD19-directed CAR-T. Patients (n=514)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
6
14
0
Order By: Relevance
“…Early relapse under these circumstances is usually associated with a median OS of <6 months. [54][55][56][57] In a more recent study, the median OS for patients failing during Day 0-30 versus >Day 30 was 1.7 versus 3.0 months respectively. 58 In multivariate analysis, predictors of OS were high lactate dehydrogenase (LDH) at infusion, time to CAR T-cell failure <Day 30 and high C-reactive protein at infusion.…”
Section: Commentsmentioning
confidence: 97%
See 3 more Smart Citations
“…Early relapse under these circumstances is usually associated with a median OS of <6 months. [54][55][56][57] In a more recent study, the median OS for patients failing during Day 0-30 versus >Day 30 was 1.7 versus 3.0 months respectively. 58 In multivariate analysis, predictors of OS were high lactate dehydrogenase (LDH) at infusion, time to CAR T-cell failure <Day 30 and high C-reactive protein at infusion.…”
Section: Commentsmentioning
confidence: 97%
“…Nonetheless, data on safety, activity, and outcomes of allo-HSCT after CAR T-cell therapy are still limited. 56,57,59,73,89 In a recent multicentre retrospective study, 57 88 patients with R/R DLBCL (median age 54 years) received an allo-HSCT after anti-CD19 CAR Tcell therapy failure. The median (range) time between CAR T-cell therapy and allo-HSCT was 255 (63-753) days.…”
Section: Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis also concluded that early relapse was associated with poorer outcomes. 15 In summary, those that have PD after CAR-T therapy have a dismal prognosis, especially those who progress early.…”
Section: Ou Tcom E S Of R /R DL Bcl a F Ter Ca R-t Th Er A Pymentioning
confidence: 99%